Being successful in school: A case study of the Orang Asli (Aboriginal People) of Malaysia - Badli Esham Ahmad; Mohd Amli Abdullah; Tengku Intan Suzila Tengku Shariff; Mohd Yusri Mohamad Nor; Mohd Rozaidi Ismail; Nor Farah Liyana Mohd Akhir (Institute of Advanced Engineering and Science, 2022)
The Orang Asli have been marginalized in many aspects including education. Despite the various support and assistance provided by the government, their development in the educational process is still lagging. However, there are cases of Orang Asli children who have managed to complete their education. The objective of the study is to identify the success factors that help the Orang Asli to be successful in their education. The research is exploratory research using qualitative method, with semi structured interviews as the primary data collection. The respondents are Orang Asli children who have completed their tertiary education. The study found that motivation and the right environment are the two important factors that contributed to the success of the respondents in the study. Environment factor is inclusive of parental, familial and societal contribution to the development of the Orang Asli education. Hence, providing the right motivation and creating the correct environment for the Orang Asli children would help them to complete their education. However, the findings are limited to the selected Orang Asli tribes and cannot be generalized to the whole Orang Asli in the country. Nonetheless, the findings provided relevant insights into the Orang Asli education and can serve as a platform for future studies.